TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN POLI UMUM DI KLINIK PRATAMA DIPONEGORO I KOTA SEMARANG BERDASARKAN DIMENSI KUALITAS - Asti, Helwa Firdausa; Budiyanti, Rani Tiyas; Kusumastuti, Wulan (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
The importance of Quality Improvement (QI) in health services is to improve the quality of health services continuously. Quality Improvement (I) can minimize complaints and achieve patient satisfaction. Based on JKN data, the Diponegoro I Primary Clinic is the primary clinic with the highest number of participants in Semarang City, namely 27,522 participants. Based on unstructured interviews with the clinic manager, the high level of complaint reports from patients because of dissatisfaction with the general poly services at the Diponegoro I Primary Clinic. The aim of this research is to analyze the level of patient satisfaction for general poly services at the Diponegoro I Primary Clinic through a balance between expectations and performance in the quality dimension (SERVQUAL). This research is a descriptive quantitative type with a cross-sectional design. The total research sample was 110 general poly patients. The data analysis technique uses the Importance-Performance Analysis (IPA) method, which consists of suitability level analysis and quadrant analysis. The research results show the level of conformity of quality dimensions is 95.78%. While each dimension is tangible (96.88%), reliability (94.17%), responsiveness (96.50%), assurance (96.54%), and empathy (94.81%). There are items should be improved by the clinic, toilet facilities cleanliness, service time by online registration system implementation, service procedure information to patients, doctor’s scheduled board updates, and SOPs implementation to inform medicine side effects to patients. The improvement to increase the level of patient satisfaction.